Teachers’ Feedback on EFL Writings from Sociocultural Perspective - Rahma Aini; Ashadi Ashadi (Indonesian Journal of EFL and Linguistics, 2022)
Writing skill is one of the difficult skills to acquire in learning a second language. Therefore, the feedback that the students receive from the teachers should be understandable and improve students’ writing skills. This study examines the teachers’ experiences in giving feedback on students’ writing performance through a sociocultural perspective. The participants of this study were 8 English teachers of junior and senior high schools in Padangsidimpuan, North Sumatra. The data were collected through online interviews and analyzed in a thematic approach by transcribing, coding, categorizing, and interpreting. The result shows that teachers prefer to use teacher-student conferencing in giving writing feedback since joint participation and transaction occur in the learning process. It is compatible with the principle of the sociocultural approach. In addition, teachers are more concerned about students’ grammatical errors rather than structure and content. It is due to students finding it difficult to implement the grammatical rules into their writings. Furthermore, unfocused corrective feedback points out a range of error types. However, the strategy is hard to implement for students with lower proficiency levels.